1999
DOI: 10.1007/pl00014338
|View full text |Cite
|
Sign up to set email alerts
|

Heparin-induced thrombocytopenia in paediatric patients – a review of the literature and a new case treated with danaparoid sodium

Abstract: Although HIT is less frequently reported in newborns and children, paediatricians should be aware of HIT in childhood as a potential complication of heparin application. The widespread practice of flushing catheters with heparin should also be debated in view of the risk of triggering the primary immune-response of HIT. In 1999, treatment options for further parenteral anticoagulation of HIT patients are danaparoid sodium (a low-molecular weight heparinoid) and lepirudin (a direct thrombin inhibitor).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(40 citation statements)
references
References 0 publications
0
40
0
Order By: Relevance
“…Although cross reactivity of danaparoid-sodium with HIT antibodies may occur, the platelet recovery in patients with HIT treated with this drug is unimpaired [45]. While hirudin and the synthetic analogue, lepirudin, are considered safe and eective treatment options in adults with HIT, little information on the use of these drugs in children is available [16,37]. Approximately 50% of the patients treated with lepirudin for HIT develop IgG antihirudin antibodies, which are occasionally associated with an unexpected increase in anticoagulant eect [15,40].…”
Section: Heparin-induced Thrombocytopeniamentioning
confidence: 99%
“…Although cross reactivity of danaparoid-sodium with HIT antibodies may occur, the platelet recovery in patients with HIT treated with this drug is unimpaired [45]. While hirudin and the synthetic analogue, lepirudin, are considered safe and eective treatment options in adults with HIT, little information on the use of these drugs in children is available [16,37]. Approximately 50% of the patients treated with lepirudin for HIT develop IgG antihirudin antibodies, which are occasionally associated with an unexpected increase in anticoagulant eect [15,40].…”
Section: Heparin-induced Thrombocytopeniamentioning
confidence: 99%
“…Most data on HIT in children are confined to case reports. [13][14][15][16][17] To date, only 1 prospective study has evaluated the incidence of HIT in newborns: Spadone et al 18 found an inci-dence of 1%, and in this group, 85% developed umbilical or aortal thrombosis.…”
mentioning
confidence: 99%
“…Most significantly, Klenner et al [29] use the term ‘survived’ and add any adverse event which occurred, Zöhrer et al [23] refer to ‘clinical recovery’, Ranze et al [30] refer to ‘positive outcome’, while Newall et al [27] describe the actual clinical events as do the reviews of Spinler and Dager [31] and Smythe [32] for adult treatment outcomes. These differences confuse collation and comparison of the reports of the available treatment options since both ‘survived’ and ‘recovery’ include certain clinical/adverse events subjectively and, as with mere descriptions of specific events, many do not take the individual clinical circumstances surrounding these events into account.…”
Section: Discussionmentioning
confidence: 99%